Research on the "Problem-Centred Theory" Pedagogy to Improve the Clinical Thinking Ability of Medical Students - Wu, Zhifu; Hu, Liyun (Indian Journal of Pharmaceutical Education and Research, 2023)
With the advent of the era of a knowledge economy, the teaching model of the problem-centred theory is widely concerned. This paper applies this teaching mode, takes the typical "abdominal pain" case as the problem centre, carries out the scenario design and teaching analysis, and explores the mode and way to improve the clinical thinking ability of medical students. Based on discussing the principles of problem situation design (including inspiration, vitality, conflict and interest), five modules of the application of problem-centred theory are innovatively proposed. 1. Create a situation, throw problems, find problems, and catch problems. 2. Grasp the main aspects of the contradiction, grasp the stipulations of the matter, and clarify the crux and essence of the problem (what disease the patient has) 3. Determine the severity and difficulty of the problem. 4. Under the teacher’s guidance, propose the solution, implement and draw conclusions. 5. Probe and trace the source, get to the bottom of the problem, and study the root cause of the problem.
Keywords: Problem-centred theory; Diagnosis; Clinical thinking; Medical education